1)0,84/2,1=0,4
2)3,5*0,18=0,63
3)0,4+0,63=1,03
4)1,03-0,08=0,95
<span>(63118-41873):35*0*5794+x=318106:53</span>
7+|х+3|=49
|х+3|=49-7
|х+3|=42
х+3≥0....................х+3<0
х+3=42.................-(х+3)=42
х=42-3.................-х-3=42
х=39...................-х=42+3
............................-х=45
............................х=-45
Ответ: х=39, х=-45
8х+5х= 72-33
13х=39
х=39:13
х=3
1/3х+1=2-1/6х
1/3х+1/6х=2-1
1/3х домножаем на 2
2/6х+1/6х=1
3/6х=1
х=1/1/3/6
х=1/1*6/3
х=6/3
х=2
1/4х-3=1/8х+5
1/4х-1/8х=3+5
1/4 домножаем на 2
2/8х-1/8х=8
1/8х=8
х=64
вроде так